Temporal comparison theory and elderly satisfaction with their body: a preliminary study - Barreto, Philipe de Souto (Revista brasileira de geriatria e gerontologia, 2012)
OBJECTIVES: Studies on body satisfaction have been neglecting a possible contribution of temporal comparisons (TC) for determining people's satisfaction with their body. The purpose of this work is to provide preliminary data on the usefulness of TC theory in determining body satisfaction in elderly individuals. METHODS: Participants were 18 functionally limited elderly adults, aged 68-90 years. After receiving three theory-related stimuli (social comparison, temporal comparison, and self-schema), they completed two scales: a scale on satisfaction with body functioning and a scale on body appearance satisfaction. RESULTS: Satisfaction with body functioning and satisfaction with body appearance did not differ among theory-related stimuli. TC-related correlations were stronger than the other theory-related correlations, even when adjusted for confounding variables. CONCLUSIONS: Our results suggest that TC theory may be a useful framework for explaining body satisfaction in the elderly. Studies on this subject should be encouraged. However, further research is needed before any conclusion can be drawn. OBJETIVOS: Estudos sobre a satisfação corporal têm negligenciado uma possível contribuição da teoria de comparação temporal a fim de determinar a percepção que os idosos têm do próprio corpo. O objetivo deste trabalho é estudar a utilidade da teoria de comparação temporal na determinação da satisfação corporal de idosos. MÉTODOS: Dezoito idosos, com idade entre 68 e 90 anos, e possuindo certo grau de limitação física, participaram do estudo. Depois de receberem estímulos relacionados a três teorias (comparação social, comparação temporal e self-schema), os participantes completaram uma escala de satisfação com a função física e uma escala de satisfação com a aparência. RESULTADOS: A satisfação corporal não diferiu entre os estímulos relacionados às três teorias aplicadas. Correlações relacionadas à teoria de comparação temporal foram superiores às correlações relacionadas às outras teorias, mesmo quando as correlações foram ajustadas por certas variáveis de confusão. CONCLUSÕES: Estes resultados sugerem que a teoria CT parece ser útil para explicar a satisfação corporal de idosos. Estudos sobre este assunto devem ser encorajados a fim que se possam desenhar conclusões sobre bases sólidas.